129k views
1 vote
Don’t know where to start

Don’t know where to start-example-1
User Eyonna
by
5.7k points

2 Answers

5 votes
This might help but I say in my mind what letter came first in the alphabet and that’s the letter I go with first
User Kudlur
by
5.9k points
7 votes

Answer:

y = -3x; the const. of prop. is -3.

Explanation:

Recall: a proportional relationship satisfies y = kx, where k is the constant of proportionality.

In this particular example we see that (-3)(-2) = 6, (-3)(1) = -3, and (-3)(2) = -6.

This confirms adherence to the equation of a proportional relationship. The constant of proportionality here is -3.

The function governing the table is y = -3x.

User Perseids
by
6.2k points